Amplifikasi Gen Penyandi Protein Fusion Virus Tetelo dari Spesimen Lapangan dengan Metode OneStep RT-PCR. (AMPIFICATION OF FUSION PROTEIN ENCODING GENE OF NEWCASTLE DISEASE VIRUS FROM FIELD SPECIMENS BY ONESTEP RT-PCR METHOD) - Haryanto, Aris; Kristiawan, David; Irianingsih, Sri Handayani; Yudianingtyas, Dini Wahyu (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
Tetelo or Newcastle Disease (ND)  virus is belong to the family Paramyxoviridae, which has a singlestranded RNA (ss RNA) genome and it has viral envelope.  The viral envelope consists of two majorproteins, namely Haemagglutinin/Neuraminidase (H/N) and Fusion (F) protein. Molecular diagnosticmethods OneStep RT-PCR is a commonly diagnostic tool that used to diagnose of Tetelo in poultry. In thisstudy the diagnosis of Tetelo is accomplished by amplification of F protein encoding gene of Tetelo virusdirectly from field specimens without inoculation and propagation of Tetelo virus into embryonated chickeneggs. The objective of this study is to conduct rapid diagnosis of Tetelo virus directly from the field specimensbased on the amplification of the F gene by a OneStep RT-PCR method, so that the results of this study canbe used to assist in the identification of Tetelo virus directly from the field specimens. The results showedthat from the 15 samples of virus which isolated from tracheal swabs of clinical poultry showing symptomsof Tetelo virus infection, a total of 12 samples from 15 tested sampels (80%) are positive tested for Tetelovirus infection. They were indicated by the amplification product of DNA fragments in size of 362 bp.OneStep RT-PCR is a method for rapid and effective diagnosis which can be used  to diagnose of Tetelovirus directly from field specimens.
Keywords: Tetelo virus, F gene, field specimen, RT-PCR